Developing a readiness evaluation framework for public hospital-led digital home nursing services in China: a Delphi-AHP study - Yuzhe Wang; Zimin Wang; Yingchun Liu; Guiming Yan; Fang Hu; Xiaodan Wu; Tianzhi Yu (BMC Nursing, 2026)
Abstract Background Internet Plus Nursing Services have become an important public hospital-led model for extending professional nursing care from hospitals to patients’ homes through digital platforms in China. Although previous studies have examined service quality, patient experience, nurse participation, and platform functions, little attention has been paid to whether public hospitals possess the system readiness required to deliver safe, sustainable, traceable, and accountable digital home nursing. This study aimed to develop a readiness evaluation framework for public hospital-led digital home nursing services and determine the relative priority of its indicators. Methods Porter’s Five Forces model was contextualized as an organizing framework for readiness domains after consideration of established health-system and implementation perspectives. An initial indicator pool was developed through literature review, policy document analysis, and preliminary expert consultation. Two rounds of Delphi consultation were conducted to refine the second- and third-level indicators. A score-informed adaptation of the analytic hierarchy process (AHP) was subsequently used to estimate indicator weights from the second-round Delphi importance scores. Expert authority, consensus, judgment-matrix consistency, and the sensitivity of the resulting priorities to small changes in the score-to-Saaty conversion boundaries were evaluated. Results 52 experts participated in the first Delphi round, and 48 completed the second round. The expert authority coefficient was 0.74. Kendall’s W increased from 0.150 to 0.196 for the second-level indicators and from 0.144 to 0.205 for the third-level indicators, with all tests statistically significant ( P < 0.001). The final framework comprised five first-level domains, 14 second-level indicators, and 43 third-level indicators. Workforce and Digital Platform Infrastructure received the highest first-level weight (32.29%), followed by Patient Adoption, Payment, and Value Recognition (24.47%) and Operational Quality, Safety, and Accountability (18.54%). All applicable AHP judgment matrices met the consistency criterion, with CR values ranging from 0.0088 to 0.0516. Sensitivity analyses showed that small shifts in the conversion boundaries did not materially alter the overall priority structure. Conclusions This study developed a structured readiness evaluation framework for public hospital-led digital home nursing services in China. The findings highlight workforce and digital platform infrastructure, patient adoption and payment support, and operational quality, safety, and accountability as priority readiness conditions. The framework provides a structured reference for assessing the conditions required for safe, traceable, and sustainable digital home nursing, while further validation using multicenter and real-world service data is warranted.